An assessment of carbon and nutrient limitations in the formation of the southern Andes tree line. (5th December 2016) - Fajardo, Alex; Piper, Frida I.
Summary: Although the principal mechanism determining tree line formation appears to be carbon (C)‐sink limitations due to low temperatures, few studies have assessed the complementary role of reduced soil nutrient availability with elevation. We tested the hypothesis that nutrient (especially nitrogen, N) limitations at tree line may directly (via C‐source) or indirectly (via C‐sink) reduce the growth of a winter deciduous tree line species. If a shortage of soil N with elevation is involved in tree line formation, it should occur in two alternative ways: (i) through sink limitations because N is required for tissue formation, which would indirectly limit C investments (N decreases and C reserves increase with elevation), and (ii) through C limitations because this would lead directly to a reduction of photoassimilates (N and C reserves decrease with elevation). In testing our hypothesis, we analysed tree growth rates (basal area increment), twig non‐structural carbohydrate (NSC) and N concentrations, leaf N, phosphorus (P), N:P ratio concentrations, and soil nutrient levels (NO3 −, NH4 +, Olsen–P) in four disparate climate and soil Nothofagus pumilio tree lines spanning 18 degrees of latitude in the southern Andes of Chile. We found a significant decrease in tree growth with elevation. Twig NSC concentrations pooled across locations also decreased significantly with elevation (starch constituted most of the NSC and was highly responsible for the negative trend), although this trend was mostly driven by the northernmost locations. Contrary to soil N availability, leaf N and P concentrations increased significantly with elevation. Twig N concentrations, soil P and leaf N:P ratios did not change with elevation. Synthesis . The elevational decrease in NSC concentrations supports C‐source limitation in N. pumilio trees at tree line elevation. In the light of this, we assert that the current global explanation for tree line formation (C‐sink‐limitation driven by low temperatures) must be revisited. Given that leaf N and P concentrations increased and twig N concentrations did not change with elevation, nutrient limitation is not likely to be involved in the C‐limitations and could not therefore be an explanation for tree line formation. Abstract : The elevational decrease in NSC concentrations supports C‐source limitation in N. pumilio trees at tree line elevation. In the light of this, we assert that the current global explanation for tree line formation (C‐sink‐limitation driven by low temperatures) must be revisited. Given that leaf N and P concentrations increased and twig N concentrations did not change with elevation, nutrient limitation is not likely to be involved in the C‐limitations and could not therefore be an explanation for tree line formation. Editor's Choice